Primer registro de Eudinopus dytiscoides (Schreibers, 1802) (Coleoptera: Scarabaeidae: Scarabaeinae: Canthonini) para Bolivia. - Vidaurre, Tito; Ledezma, Julieta; Vaz-de-Mello, Fernando Z. (Instituto de Ecología, A.C., 2009)
Eudinopus dytiscoides (Schreibers, 1802) is reported for the first time from Bolivia. It was previouslyknown only from Argentina.